PENERAPAN MODEL PEMBELAJARAN BERBASIS MASALAH DENGAN PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN AKTIVITAS BELAJAR, HASIL BELAJAR DAN SIKAP ILMIAH SISWA SMA - Wenda Dwi Meilesri; Indra Sakti; Desy Hanisa Putri (UNIB Press, 2017)
The purposes of this classroom action research were to enhance students’ learning activity, learning outcomes and student's scientific attitude on the concept of static fluid. Subjec was 35 students in X grade. The results of the study indicated that students' learning activities on the first cycle with an average score of 41 (the active category), the second cycle with an average score of 45 (active category), the third cycle with an average score of 48 with an average score of 48 (the active category) and the fourt cycle of with an average score of 48 (the active category). The result of cognitive domain was 71,4%students in reaching mastery learning (cycle I), increased to 82,9% mastery learning (cycle II), increased to 85,7% (cycle III), obtained learning mastery equal to 85,7%, and increased to 91,4% (the cycle IV). The results of psychomotoric reached 80,7 (cycle I), became to 83,0 (cyle II), increased to 83,7 (Cycle III) and increased to 85,5 (cycle IV). There were 21 students reached the good category of scientific attitude in the first cycle, 27 students in the second cycle, 32 students in the third cycle 33 students in the fourth cycle. Based on the result of the research, it is concluded that the implementation of problem based learning with scientific approach can increase the learning activities, the learning result and scientific attitude on the concept of statics fluid.